(untitled) (Research, Society and Development, 2020)
To evaluate the level of health literacy related to HIV/Aids among the elderly who attend a coexistence program in a metropolis in northern Brazil. Descriptive, quantitative and qualitative research whose data were collected by using the questionnaire "Health Literacy" by Wang et al., in the Brazilian version. The sample consisted of 173 elderly people. Collected by interviews, data were analyzed by classifying them in the following dimensions. 1) Interest and concern with HIV/Aids. 2) Search for information. 3) Understanding information on HIV/Aids prevention. 4) Sharing information on HIV/AIDS prevention. 5) Information repercussion. There was a low level of Health Literacy among the elderly, in all dimensions of the construct, inducing to relate it to the low socioeconomic and educational level found. The low level of Health Literacy among the elderly is a clear gap in health education. The results support the review of local health programs to combat HIV/AIDS among the elderly, and alert to innovative educational actions that make the elderly’s role more autonomous for safer and healthier sex life.